Survival Estimates of Atraumatic Restorative Treatment versus Traditional Restorative Treatment - Abdulaziz Abdullah Alkhalaf; Abdullah Ahmed Al Zaid; Mohammed Eid Aljohani; Fayyad Saud Almogren; Abdullah Abdulrahman Alsenaidy; Muhannad Omar Albabtain; Essam Masoud Alhaidri; Khalaf Mutheeb Almutairi; Fahad Abdulaziz Alomayrah; Khaled Saad Alkhaldi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: ART is a minimally invasive procedure that is typically performed without the utilization of anesthetic or electrically powered apparatus, and only decayed tissue is removed using hand instruments. Aim: We performed this investigation to estimate the survival of a traumatic restorative treatment versus a traditional restorative treatment. Materials and methods: We conducted a search of the PubMed/MEDLINE, Scopus, Web of Science, and Open Grey databases up to 2020. We included research that assessed ART restorations and had survival rate data. The possibility of bias has been assessed using the Rob 2.0 and ROBINS-I tools. Meta-analyses have been carried out with the survival rate of 1ry and permanent teeth as the result. Subgroup analyses have been conducted for the setting and type of cavity (occlusal or multi-surface). Results: Survival Rates: ART/HVGIC shows higher survival rates than traditional methods in most cases, especially in the single restoration category. Traditional restorative treatment shows higher cumulative survival rates at both six months and 12 months compared to ART. Both treatment methods experienced a decrease in survival rates from 6 months to 12 months. Conclusion: We concluded from our study that the atraumatic restorative treatment (ART) method utilizing high-viscosity glass-ionomer cement (HVGICs) may be considered as a replacement for traditional restorations.